Glass fiber reinforced halogen-free flame-retardant PBT / PC (polybutylene terephthalate / polycarbonate) alloy material with high dimensional stability

By adding modified heat-resistant agents, mica and hollow glass microbeads to the PBT/PC alloy material, and carrying out specific pretreatment and mixing extrusion processes, the problem of dimensional instability of PBT/PC alloy material under high temperature conditions is solved, and the heat resistance and production efficiency of the material are significantly improved.

CN119708777APending Publication Date: 2025-03-28HANGZHOU ZETONG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411910310.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing PBT/PC alloy materials are difficult to maintain dimensional stability under high temperature conditions, and lack effective technical means to improve heat resistance and improve production efficiency.

Method used

By adding modified heat-resistant agents, mica, hollow glass microbeads and other components to the PBT/PC alloy material, and carrying out specific pretreatment and mixing extrusion processes, high-dimensional stability glass fiber reinforced halogen-free flame-retardant PBT/PC alloy material is prepared.

Benefits of technology

It significantly improves the mechanical properties, dimensional stability, heat resistance and corrosion resistance of the material, reduces waste rate and energy consumption, and improves the consistency of processing efficiency and product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205478860000131
    Figure BDA0005205478860000131
Patent Text Reader

Abstract

The invention discloses a high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material, and relates to the technical field of PBT / PC alloy preparation, the raw materials comprise the following components by mass: 35-60 parts of PBT, 30-40 parts of PC, 2-10 parts of a modified heat resistant agent, 1-15 parts of an antioxidant, 0.1-6 parts of a heat stabilizer, 0.2-3 parts of a lubricant, 0.2-3 parts of a halogen-free flame retardant, 2-6 parts of mica, and 5-40 parts of glass fiber. The glass fiber reinforced PBT / PC alloy material is processed and prepared according to a set proportion and a set preparation sequence, the PBT / PC material with high dimensional stability is finally obtained, diisocyanate, hydroxyalkyl terminated polydimethylsiloxane and a hexaalkoxy silane coupling agent are compounded according to a certain proportion to prepare a modified heat-resistant agent, and the modified heat-resistant agent is added into the glass fiber reinforced PBT / PC alloy material to prepare the glass fiber reinforced PBT / PC alloy material. According to the PBT / PC alloy material disclosed by the invention, the overall heat resistance of the PBT / PC alloy material is improved while the interfacial compatibility among different materials is improved, and the prepared PBT / PC alloy material has better dimensional stability at different temperatures due to the proportion of PBT and PC and is not easy to change in size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PBT / PC alloy preparation, in particular to a glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability. Background Art

[0002] PBT / PC alloy material is a mixture of two polymer materials, polycarbonate and polybutylene terephthalate, through physical or chemical methods. It has good heat resistance, impact strength and tolerance, and is widely used in many fields, including automotive parts, electronic and electrical product casings, power tool casings, and window frames and other building materials. The existing PBT / PC alloy material has general heat resistance and it is difficult to maintain dimensional stability for a long time under high temperature conditions.

[0003] The defects of existing PBT / PC alloy materials are:

[0004] 1. Patent document CN113817297B discloses a high-impact, high-flame-retardant and weather-resistant PBT / PC alloy material. It mainly considers that under strong ultraviolet rays, high temperature and humidity or low temperature freezing conditions, it still has high flame retardant properties with long aging resistance, high fluidity and high impact resistance, but does not consider how to improve the overall heat resistance of the PBT / PC alloy material, thereby improving the dimensional stability of the alloy material;

[0005] 2. Patent document CN105086385B discloses a high impact flame retardant PBT / PC alloy material and a preparation method thereof. It mainly considers how to prepare a material with excellent flame retardancy and high impact resistance and environmental safety, but does not consider how to further improve the heat resistance of the material and improve production efficiency;

[0006] 3. Patent document CN104559105B discloses a low-shrinkage, high-strength PBT / PC alloy material for 3D printing. It mainly considers how to eliminate stress points with too low density to improve the strength of the product, but does not consider how to pre-treat the raw materials to ensure the consistency of the quality of the final product.

[0007] 4. Patent document CN115627063B discloses a flame-retardant PBT / PC alloy material and its preparation method and application. It mainly considers making the material have excellent flame retardant properties and impact toughness, while effectively improving the color stability of the material during the injection molding process and solving the injection molding yellowing problem of the material. It does not consider how to improve the flame retardant properties of the product. Summary of the invention

[0008] The object of the present invention is to provide a glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability to solve the problems raised in the above background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: a high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material, wherein the raw materials thereof include the following components by weight: 35-60 parts of PBT, 30-40 parts of PC, 2-10 parts of modified heat resistant agent, 1-15 parts of antioxidant, 0.1-6 parts of heat stabilizer, 0.2-3 parts of lubricant, 0.2-3 parts of halogen-free flame retardant, 2-6 parts of mica, 5-40 parts of glass fiber, 0.1-2 parts of anti-ultraviolet agent, 5-20 parts of inorganic filler, 0-2 parts of hollow glass microspheres and 0.5-3 parts of ester exchange inhibitor;

[0010] The glass fiber reinforced PBT / PC alloy material is prepared by mixing PBT, PC, modified heat resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, UV inhibitor, inorganic filler, hollow glass microsphere and ester exchange inhibitor.

[0011] Preferably, the particle size range of the hollow glass microspheres is 5-10 mm, the mica is one or more of muscovite, phlogopite, biotite, lepidolite, and sericite, and its particle size range is 1-100 μm, the melt index of the PC is 8-12 g / 10 min, the number average molecular weight is 35000-40000, and the intrinsic viscosity of the PBT is 1 dL / g at room temperature.

[0012] Preferably, the inorganic filler is a mixture of talc and calcium carbonate in a mass ratio of (1-3):1, wherein the particle size of the talc is 1300-2000 mesh, and the particle size of the calcium carbonate is 5-15 μm.

[0013] Preferably, the halogen-free flame retardant is prepared by mixing OP1230 flame retardant and melamine polyphosphate in a mass ratio of (13-15):(3-5), and the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of (1-2):1:1.

[0014] Preferably, the glass fiber has a diameter of 7-10 μm and a length of 1-2 mm.

[0015] Preferably, the antioxidant is one or more of BASF Irganox B215, Clariant Hostanox P-EPQ, antioxidant 1076 and antioxidant 168, and the heat stabilizer is one or more of calcium zinc composite heat stabilizer, TPP and TNPP.

[0016] Preferably, the preparation method of the high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material is as follows:

[0017] Step S1: raw material pretreatment: drying PC and PBT, and modifying the glass fiber to obtain modified glass fiber;

[0018] Step S2: Mixing and extruding: PBT, PC, modified heat-resistant agent, antioxidant, lubricant, halogen-free flame retardant, mica, glass fiber, UV-resistant agent, inorganic filler, hollow glass microspheres and transesterification inhibitor are sequentially placed in a high-speed mixer for thorough mixing, and then melt-blended and extruded using an extruder to form pellets;

[0019] Step S3: stretching and cooling: stretching and pulling the pellets extruded from the extruder, and then placing the stretched pellets in a cooling water tank for cooling. When the temperature of the pellets drops to room temperature, the cooled pellets are air-dried, and finally placed in a pelletizer for granulation to obtain a PBT / PC alloy material.

[0020] Step S4: quality control: performing quality inspection on the PBT / PC alloy material prepared in step S3;

[0021] Step S5: Packaging: The prepared PBT / PC alloy material is sealed and packaged with moisture-proof, dust-proof and oxidation-proof packaging materials, and is sealed by heat sealing, and a label is affixed to the package, and it is temporarily stored in a dry, ventilated and light-proof place.

[0022] Preferably, the step S1 further includes the following steps:

[0023] Step S11: placing PC and PBT in a constant temperature blast drying oven for drying at a temperature of 80-90° C. for 1-1.5 hours;

[0024] Step S12: using a silane coupling agent to perform surface treatment on the glass fiber, and then using nanoparticles to modify the surface of the glass fiber.

[0025] Preferably, the step S2 further includes the following steps:

[0026] Step S21: Mixing treatment: firstly put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor into a high-speed mixer, stir at 800-900 rpm for 30-40 min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue to stir at 800-900 rpm for 20-30 min at a heating temperature of 260-300° C., cool down after mixing, when the temperature drops to 100-150° C., add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 900-1000 rpm for 30 min at a constant temperature of 100-150° C., and obtain a uniformly stirred mixture;

[0027] Step S22: Extrusion process: Add the mixture in step S21 into a parallel twin-screw extruder, and add a heat stabilizer from the fiber inlet, and perform melt blending and extrusion through the extruder to form particle strips, wherein the extrusion temperature is 240-260°C and the rotation speed is 800rpm.

[0028] Preferably, the step S4 further includes the following steps:

[0029] Step S41: Perform a melt index test at 280°C and 5KG according to ISO-1133 standard, perform a heat deformation temperature test according to ASTMD-648 standard, and make a 100mm*10mm*4mm rectangular parallelepiped specimen of PBT / PC alloy material according to ASTMD955 standard, place it in a standard environment of temperature of 23°C and relative humidity of 50% and temperature of 80°C and relative humidity of 50% for 2 days, and measure the volume size change rate of the alloy material;

[0030] Step S42: Perform a tensile strength test according to ASTM D-638 and a bending strength test according to ASTM D-790;

[0031] Step S43: Perform a vertical burning level test according to the UL94 standard and a smoke density level test according to the GB / T-8627 standard.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The glass fiber reinforced PBT / PC alloy material of the present invention is processed and prepared according to a set ratio and preparation sequence to finally obtain a PBT / PC material with high dimensional stability. The modified heat-resistant agent is prepared by compounding diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a certain ratio. While improving the interface compatibility between different materials, the overall heat resistance of the PBT / PC alloy material is improved. The ratio of PBT to PC makes the prepared PBT / PC alloy material have good dimensional stability at different temperatures and is not prone to dimensional changes.

[0034] 2. The present invention can significantly improve the mechanical properties, dimensional stability, heat resistance and corrosion resistance of the product by adding specific mica and hollow glass microspheres. The two-dimensional sheet structure of mica can play a role of plane reinforcement in plastics, thereby improving the bending modulus and tensile strength of the product, and may also help to reduce the molding shrinkage of the product and prevent warping deformation. In addition, mica and hollow glass microspheres have good thermal stability, can increase the heat deformation temperature and high temperature creep resistance of the material, make the product not easy to decompose at high temperature, and improve the flame retardancy and heat deformation temperature of the product to a certain extent. In addition, since the hollow glass microspheres have excellent activity performance, the production efficiency can also be improved and energy consumption can be reduced.

[0035] 3. The present invention ensures the consistency of raw material quality by pretreating PBT and PC raw materials, thereby ensuring the consistency of quality and performance of the subsequently prepared PBT / PC alloy material, reducing the scrap rate to a certain extent, thereby improving the overall processing efficiency, and using silane coupling agent and nanoparticles to modify the glass fiber. The silane coupling agent adheres to the surface of the glass fiber and forms a strong covalent bond through chemical reaction, thereby improving the interface strength between the glass fiber and the matrix material. The nanoparticles can improve the thermal stability, weather resistance and mechanical properties of the composite material. The silane coupling agent and the nanoparticles act together on the glass fiber to improve the interface compatibility and bonding force of the glass fiber. When the PBT / PC alloy material is subsequently prepared, it can be better bonded to other materials, thereby improving the dimensional stability of the finally prepared PBT / PC alloy material.

[0036] 4. The present invention prepares a halogen-free flame retardant by mixing OP1230 flame retardant and melamine polyphosphate in a certain proportion, which improves the flame retardant properties of PBT / PC alloy materials without causing any impact on the environment. Adding glass fiber to PBT / PC can improve the strength and rigidity of the material, thereby further improving the performance stability of the product. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention provides a glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability, and a preparation method of the glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability as follows:

[0039] Step S1: Raw material pretreatment: PC and PBT are placed in a constant temperature blast drying oven for drying at 80°C for 1.5 hours, and the glass fiber is surface treated with a silane coupling agent, and then the surface of the glass fiber is modified with nanoparticles to obtain modified glass fiber.

[0040] Step S2: Mixed extrusion: PBT, PC, inorganic filler, lubricant and transesterification inhibitor are first placed in a high-speed mixer, stirred at 800-900 rpm for 30-40 min at room temperature, then glass fiber, antioxidant, mica and hollow glass microspheres are added thereto, and stirred at 800-900 rpm for 20-30 min at a heating temperature of 260-300°C. After mixing, the mixture is cooled, and when the temperature drops to 100-150°C, the modified heat-resistant agent, halogen-free flame retardant and UV-resistant agent are added to the high-speed mixer. , stirring at a speed of 900-1000 rpm for 30 minutes at a constant temperature of 100-150°C to obtain a uniformly stirred mixture, then adding the mixture into a parallel twin-screw extruder, and adding a heat stabilizer from the fiber inlet, and extruding the mixture through the extruder to form pellets, wherein the extrusion temperature is 240-260°C, the rotation speed is 800 rpm, and the mass ratio of PBT, PC, modified heat resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, UV inhibitor, inorganic filler, hollow glass microspheres and ester exchange inhibitor is (35~60):(30~40):(2~10):(1~15):(0.1~6):(0.2~3):(0.2~3):(2~6):(5~40):(0.1~2):(5~20):(0~2):(0.5~3), the particle size range of hollow glass microspheres is 5-10mm, the particle size range of mica is 1-100μm, the melt index of PC is 8-12g / 10min, the number average molecular weight is 35000-40000, the intrinsic viscosity of PBT is 1dL / g at room temperature, and the inorganic filler is The talc powder and calcium carbonate are mixed in a mass ratio of (1-3):1, the particle size of the talc powder is 1300-2000 mesh, the particle size of the calcium carbonate is 5-15 μm, the halogen-free flame retardant is prepared by mixing an OP1230 flame retardant and melamine polyphosphate in a mass ratio of (13-15):(3-5), the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of (1-2):1:1, and the diameter of the glass fiber is 7-10 μm and the length is 1-2 mm;

[0041] Step S3: stretching and cooling: stretching and pulling the pellets extruded from the extruder, and then placing the stretched pellets in a cooling water tank for cooling. When the temperature of the pellets drops to room temperature, the cooled pellets are air-dried, and finally placed in a pelletizer for granulation to obtain a PBT / PC alloy material.

[0042] Step S4: quality control: performing quality inspection on the PBT / PC alloy material prepared in step S3;

[0043] Step S5: Packaging: The prepared PBT / PC alloy material is sealed and packaged with moisture-proof, dust-proof and oxidation-proof packaging materials, and is sealed by heat sealing, and a label is affixed to the package, and it is temporarily stored in a dry, ventilated and light-proof place.

[0044] Further, the value in step S2 is changed, and steps S1 and S5-40 are performed, and the performance of the prepared glass fiber reinforced PBT / PC alloy material is evaluated.

[0045] Embodiment 1:

[0046] Step S2: mixed extrusion: first put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor in a high-speed mixer, stir at 850rpm for 40min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue stirring at 850rpm for 30min under the condition of heating temperature of 280℃, cool down after mixing, when the temperature drops to 120℃, add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 900rpm for 30min under the condition of constant temperature of 120℃ to obtain a uniform mixture, then add the mixture into a parallel twin-screw extruder, add the heat stabilizer from the fiber inlet, and perform melt blending and extrusion through the extruder to form granular strips, wherein the extrusion temperature is 240℃, the rotation speed is 800rpm, and PBT, PC, modified heat-resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, anti-ultraviolet The mass ratio of the external radiation agent, inorganic filler, hollow glass microspheres and ester exchange inhibitor is 40:36:5:11:2.4:1.5:1:2:30:0.8:7:0.5:1.3. The particle size range of the hollow glass microspheres is 6 mm, the particle size range of the mica is 20 μm, the melt index of PC is 10 g / 10 min, the number average molecular weight is 36000, the intrinsic viscosity of PBT is 1 dL / g at room temperature, and the inorganic filler is talc and calcium carbonate in accordance with the mass ratio. The particle size of talcum powder is 1500 mesh, the particle size of calcium carbonate is 7μm, the halogen-free flame retardant is prepared by mixing chitosan, red phosphorus masterbatch, aluminum hydroxide powder and silicon dioxide in a mass ratio of 2:0.2:1:0.7, the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of 2:1:1, the diameter of the glass fiber is 8μm, and the length is 1mm.

[0047] Further, the test showed that the melt index was 10.3, the heat deformation temperature was 126.3°C, the tensile strength was 136MPa, the bending strength was 156MPa, the flame retardant grade was V0, the volume size change rate at 23°C was 0.26%, and the volume size change rate at 80°C was 0.31%.

[0048] Embodiment 2:

[0049] Step S2: mixed extrusion: first put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor in a high-speed mixer, stir at 850rpm for 40min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue stirring at 850rpm for 30min under the condition of heating temperature of 280℃, cool down after mixing, when the temperature drops to 120℃, add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 900rpm for 30min under the condition of constant temperature of 120℃ to obtain a uniform mixture, then add the mixture into a parallel twin-screw extruder, add the heat stabilizer from the fiber inlet, and perform melt blending and extrusion through the extruder to form granular strips, wherein the extrusion temperature is 240℃, the rotation speed is 800rpm, and PBT, PC, modified heat-resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, anti-ultraviolet The mass ratio of the external radiation agent, inorganic filler, hollow glass microsphere and ester exchange inhibitor is 45:36:5:11:2.4:1.5:1:2:30:0.8:9:0.7:1.3. The particle size range of the hollow glass microsphere is 6 mm, the particle size range of the mica is 20 μm, the melt index of PC is 10 g / 10 min, the number average molecular weight is 36000, the intrinsic viscosity of PBT is 1 dL / g at room temperature, and the inorganic filler is talcum powder and calcium carbonate according to the mass ratio. The particle size of talcum powder is 1500 mesh, the particle size of calcium carbonate is 7μm, the halogen-free flame retardant is prepared by mixing chitosan, red phosphorus masterbatch, aluminum hydroxide powder and silicon dioxide in a mass ratio of 2:0.3:1:0.7, the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of 2:1:1, the diameter of the glass fiber is 8μm, and the length is 1mm.

[0050] Further, the test showed that the melt index was 10.1, the heat deformation temperature was 129.2°C, the tensile strength was 141MPa, the bending strength was 161MPa, the flame retardant grade was V0, the volume size change rate at 23°C was 0.21%, and the volume size change rate at 80°C was 0.24%.

[0051] Embodiment three:

[0052] Step S2: mixed extrusion: first put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor in a high-speed mixer, stir at 850rpm for 40min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue stirring at 850rpm for 30min under the condition of heating temperature of 270℃, cool down after mixing, when the temperature drops to 130℃, add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 1000rpm for 30min under the condition of constant temperature of 130℃ to obtain a uniform mixture, then add the mixture into a parallel twin-screw extruder, add the heat stabilizer from the fiber inlet, and perform melt blending and extrusion through the extruder to form granular strips, wherein the extrusion temperature is 240℃, the rotation speed is 800rpm, and PBT, PC, modified heat-resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, anti-ultraviolet agent The mass ratio of the external radiation agent, inorganic filler, hollow glass microspheres and ester exchange inhibitor is 50:36:5:11:2.4:1.5:1:4:35:0.8:13:1.4:1.3, the particle size range of the hollow glass microspheres is 6 mm, the particle size range of the mica is 30 μm, the melt index of PC is 10 g / 10 min, the number average molecular weight is 36000, the intrinsic viscosity of PBT is 1 dL / g at room temperature, and the inorganic filler is talc and calcium carbonate according to the mass ratio. The particle size of talcum powder is 1500 mesh, the particle size of calcium carbonate is 7μm, the halogen-free flame retardant is prepared by mixing chitosan, red phosphorus masterbatch, aluminum hydroxide powder and silicon dioxide in a mass ratio of 2:0.3:1:0.7, the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of 2:1:1, the diameter of the glass fiber is 8μm, and the length is 1mm.

[0053] Further, the test showed that the melt index was 9.7, the heat deformation temperature was 136.1°C, the tensile strength was 159MPa, the bending strength was 174MPa, the flame retardant grade was V0, the volume size change rate at 23°C was 0.13%, and the volume size change rate at 80°C was 0.17%.

[0054] Embodiment 4:

[0055] Step S2: mixed extrusion: first put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor in a high-speed mixer, stir at 850rpm for 40min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue stirring at 850rpm for 30min under the condition of heating temperature of 270℃, cool down after mixing, when the temperature drops to 130℃, add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 1000rpm for 30min under the condition of constant temperature of 130℃ to obtain a uniform mixture, then add the mixture into a parallel twin-screw extruder, add the heat stabilizer from the fiber inlet, and perform melt blending and extrusion through the extruder to form granular strips, wherein the extrusion temperature is 240℃, the rotation speed is 800rpm, and PBT, PC, modified heat-resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, anti-ultraviolet agent The mass ratio of the external radiation agent, inorganic filler, hollow glass microspheres and ester exchange inhibitor is 50:36:5:11:2.4:1.5:1:5:35:0.8:13:1.4:1.3, the particle size range of the hollow glass microspheres is 6 mm, the particle size range of the mica is 30 μm, the melt index of PC is 10 g / 10 min, the number average molecular weight is 36000, the intrinsic viscosity of PBT is 1 dL / g at room temperature, and the inorganic filler is talc and calcium carbonate according to the mass ratio. The particle size of talcum powder is 1500 mesh, the particle size of calcium carbonate is 7μm, the halogen-free flame retardant is prepared by mixing chitosan, red phosphorus masterbatch, aluminum hydroxide powder and silicon dioxide in a mass ratio of 2:0.3:1:0.7, the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of 2:1:1, the diameter of the glass fiber is 8μm, and the length is 1mm.

[0056] Further, the test showed that the melt index was 9.8, the heat deformation temperature was 133.2°C, the tensile strength was 157MPa, the bending strength was 168MPa, the flame retardant grade was V0, the volume size change rate at 23°C was 0.18%, and the volume size change rate at 80°C was 0.22%.

[0057] Embodiment five:

[0058] Step S2: Mixed extrusion: first put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor in a high-speed mixer, stir at 850rpm for 40min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue stirring at 850rpm for 30min at a heating temperature of 280°C, cool down after mixing, when the temperature drops to 120°C, add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 900rpm for 30min at a constant temperature of 120°C to obtain a uniformly stirred mixture, then add the mixture into a parallel twin-screw extruder, add the heat stabilizer from the fiber inlet, and melt-blend and extrude through the extruder to form granular strips, wherein the extrusion temperature is 240°C, the rotation speed is 800rpm, and PBT, PC, modified heat-resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, anti-ultraviolet agent The mass ratio of the filament, inorganic filler, hollow glass microsphere and ester exchange inhibitor is 46:36:5:11:2.4:1.5:1:10:30:0.8:14:1.4:1.3, the particle size range of the hollow glass microsphere is 6 mm, the particle size range of the mica is 40 μm, the melt index of PC is 10 g / 10 min, the number average molecular weight is 36000, the intrinsic viscosity of PBT is 1 dL / g at room temperature, and the inorganic filler is talc and calcium carbonate in accordance with the mass ratio. The particle size of talcum powder is 1500 mesh, the particle size of calcium carbonate is 7μm, the halogen-free flame retardant is prepared by mixing chitosan, red phosphorus masterbatch, aluminum hydroxide powder and silicon dioxide in a mass ratio of 2:0.3:1:0.7, the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of 2:1:1, the diameter of the glass fiber is 8μm, and the length is 1mm.

[0059] Further, the test showed that the melt index was 10.2, the heat deformation temperature was 127.1°C, the tensile strength was 151MPa, the bending strength was 162MPa, the flame retardant grade was V0, the volume size change rate at 23°C was 0.19%, and the volume size change rate at 80°C was 0.25%.

[0060] Embodiment six:

[0061] Step S2: mixed extrusion: first put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor in a high-speed mixer, stir at 850rpm for 40min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue stirring at 850rpm for 30min under the condition of heating temperature of 280℃, cool down after mixing, when the temperature drops to 120℃, add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 900rpm for 30min under the condition of constant temperature of 120℃ to obtain a uniform mixture, then add the mixture into a parallel twin-screw extruder, add the heat stabilizer from the fiber inlet, and perform melt blending and extrusion through the extruder to form granular strips, wherein the extrusion temperature is 240℃, the rotation speed is 800rpm, and PBT, PC, modified heat-resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, anti-ultraviolet The mass ratio of the external radiation agent, inorganic filler, hollow glass microspheres and ester exchange inhibitor is 36:36:5:11:2.4:1.5:1:5:30:0.8:10:1:1.3. The particle size range of the hollow glass microspheres is 6 mm, the particle size range of the mica is 40 μm, the melt index of PC is 10 g / 10 min, the number average molecular weight is 36000, the intrinsic viscosity of PBT is 1 dL / g at room temperature, and the inorganic filler is talc and calcium carbonate according to the mass ratio. The particle size of talcum powder is 1500 mesh, the particle size of calcium carbonate is 7 μm, the halogen-free flame retardant is prepared by mixing chitosan, red phosphorus masterbatch, aluminum hydroxide powder and silicon dioxide in a mass ratio of 2:0.3:1:0.7, the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and hexaalkoxysilane coupling agent in a mass ratio of 2:1:1, the diameter of the glass fiber is 8 μm, and the length is 1 mm.

[0062] Further, the test showed that the melt index was 10.8, the heat deformation temperature was 125.9°C, the tensile strength was 146MPa, the bending strength was 159MPa, the flame retardant grade was V1, the volume size change rate at 23°C was 0.20%, and the volume size change rate at 80°C was 0.27%.

[0063] Comparative Example:

[0064] The existing PBT / PC alloy material sold on the market is used as a comparative example. The test results show that the melt index is 11.8, the heat deformation temperature is 113.5°C, the tensile strength is 127MPa, the bending strength is 148MPa, the flame retardant grade is V1, the volume size change rate at 23°C is 0.29%, and the volume size change rate at 80°C is 0.34%.

[0065] The performance test results of high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy materials are as follows:

[0066]

[0067] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. High dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material, characterized by: The raw materials include the following components by weight: 35-60 parts of PBT, 30-40 parts of PC, 2-10 parts of modified heat-resistant agent, 1-15 parts of antioxidant, 0.1-6 parts of heat stabilizer, 0.2-3 parts of lubricant, 0.2-3 parts of halogen-free flame retardant, 2-6 parts of mica, 5-40 parts of glass fiber, 0.1-2 parts of UV inhibitor, 5-20 parts of inorganic filler, 0-2 parts of hollow glass microspheres and 0.5-3 parts of ester exchange inhibitor; The glass fiber reinforced PBT / PC alloy material is prepared by mixing PBT, PC, modified heat resistant agent, antioxidant, heat stabilizer, lubricant, halogen-free flame retardant, mica, glass fiber, UV inhibitor, inorganic filler, hollow glass microsphere and ester exchange inhibitor.

2. The high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material according to claim 1, characterized in that: The particle size range of the hollow glass microspheres is 5-10 mm, the mica is one or more of muscovite, phlogopite, biotite, lepidolite, and sericite, and its particle size range is 1-100 μm, the melt index of the PC is 8-12 g / 10 min, the number average molecular weight is 35000-40000, and the intrinsic viscosity of the PBT is 1 dL / g at room temperature.

3. The high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material according to claim 1, characterized in that: The inorganic filler is a mixture of talcum powder and calcium carbonate in a mass ratio of (1-3):1, wherein the particle size of the talcum powder is 1300-2000 mesh, and the particle size of the calcium carbonate is 5-15 μm.

4. The high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material according to claim 1, characterized in that: The halogen-free flame retardant is prepared by mixing an OP1230 flame retardant and melamine polyphosphate in a mass ratio of (13-15):(3-5), and the modified heat-resistant agent is prepared by mixing diisocyanate, hydroxyalkyl-terminated polydimethylsiloxane and a hexaalkoxysilane coupling agent in a mass ratio of (1-2):1:

1.

5. The high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material according to claim 1, characterized in that: The glass fiber has a diameter of 7-10 μm and a length of 1-2 mm.

6. The high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material according to claim 1, characterized in that: The antioxidant is one or more of BASF Irganox B215, Clariant Hostanox P-EPQ, antioxidant 1076 and antioxidant 168, and the heat stabilizer is one or more of calcium zinc composite heat stabilizer, TPP and TNPP.

7. A method for preparing a glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability, which is applicable to the glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability according to claims 1 to 6, characterized in that: The preparation method of the high dimensional stability glass fiber reinforced halogen-free flame retardant PBT / PC alloy material is as follows: Step S1: raw material pretreatment: drying PC and PBT, and modifying the glass fiber to obtain modified glass fiber; Step S2: Mixing and extruding: PBT, PC, modified heat-resistant agent, antioxidant, lubricant, halogen-free flame retardant, mica, glass fiber, UV-resistant agent, inorganic filler, hollow glass microspheres and transesterification inhibitor are sequentially placed in a high-speed mixer for thorough mixing, and then melt-blended and extruded using an extruder to form pellets; Step S3: stretching and cooling: stretching and pulling the pellets extruded from the extruder, and then placing the stretched pellets in a cooling water tank for cooling. When the temperature of the pellets drops to room temperature, the cooled pellets are air-dried, and finally placed in a pelletizer for granulation to obtain a PBT / PC alloy material. Step S4: quality control: performing quality inspection on the PBT / PC alloy material prepared in step S3; Step S5: Packaging: The prepared PBT / PC alloy material is sealed with moisture-proof, dust-proof and oxidation-proof packaging materials, and is sealed by heat sealing. A label is affixed to the package, and it is temporarily stored in a dry, ventilated and light-proof place.

8. The method for preparing the glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability according to claim 7, characterized in that: The step S1 further includes the following steps: Step S11: placing PC and PBT in a constant temperature blast drying oven for drying at a temperature of 80-90° C. for 1-1.5 hours; Step S12: using a silane coupling agent to perform surface treatment on the glass fiber, and then using nanoparticles to modify the surface of the glass fiber.

9. The method for preparing the glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability according to claim 7, characterized in that: The step S2 further includes the following steps: Step S21: Mixing treatment: firstly put PBT, PC, inorganic filler, lubricant and ester exchange inhibitor into a high-speed mixer, stir at 800-900 rpm for 30-40 min at room temperature, then add glass fiber, antioxidant, mica and hollow glass microspheres, continue to stir at 800-900 rpm for 20-30 min at a heating temperature of 260-300° C., cool down after mixing, when the temperature drops to 100-150° C., add modified heat-resistant agent, halogen-free flame retardant and anti-ultraviolet agent into the high-speed mixer, stir at 900-1000 rpm for 30 min at a constant temperature of 100-150° C., and obtain a uniformly stirred mixture; Step S22: Extrusion process: Add the mixture in step S21 into a parallel twin-screw extruder, and add a heat stabilizer from the fiber inlet, and perform melt blending and extrusion through the extruder to form particle strips, wherein the extrusion temperature is 240-260°C and the rotation speed is 800rpm.

10. The method for preparing the glass fiber reinforced halogen-free flame-retardant PBT / PC alloy material with high dimensional stability according to claim 7, characterized in that: The step S4 further includes the following steps: Step S41: Perform a melt index test at 280°C and 5KG according to ISO-1133 standard, perform a heat deformation temperature test according to ASTMD-648 standard, and make a 100mm*10mm*4mm rectangular parallelepiped specimen of PBT / PC alloy material according to ASTMD955 standard, place it in a standard environment of temperature of 23°C and relative humidity of 50% and temperature of 80°C and relative humidity of 50% for 2 days, and measure the volume size change rate of the alloy material; Step S42: Perform a tensile strength test according to ASTM D-638 and a bending strength test according to ASTM D-790; Step S43: Perform a vertical burning level test according to the UL94 standard and a smoke density level test according to the GB / T-8627 standard.

Citation Information

Patent Citations

  • A low-shrinkage high-strength PBT / PC alloy material for 3D printing and its preparation method and application

    CN104559105B

  • High-impact flame-retardant PBT / PC alloy material and preparation method thereof

    CN105086385B

  • A high-impact, high-flame-retardant, and weather-resistant PBT / PC alloy material

    CN113817297B

  • A flame retardant PBT / PC alloy material and its preparation method and application

    CN115627063B

Cited By

  • TPU (thermoplastic polyurethane) elastic master batch, elastic adhesive interlining and production process of TPU elastic master batch

    CN121086282A

  • TPU elastic master batch, elastic adhesive lining and production process thereof

    CN121086282B

  • Polycarbonate alloy as well as preparation method and application thereof

    CN121249118A